Determinan Ketimpangan Pendapatan di Indonesia - Shinetiara, Tania; Adry, Melti Roza (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2023)
This study aims to determine and analyze the impact of energy poverty on income inequality in Indonesia. Energy poverty in this study uses five different measures, and its relationship to income inequality is explored. This study uses secondary data sourced from the Central Statistics Agency (BPS) in Indonesia, which uses non-linear panels data regression analysis with the Fixed Effect Model (FEM) method. The data set consists of 34 provinces in Indonesia in 2011-2020. The results of this study show that the energy poverty variable described using five measurement indicators is only one of which is proven to have a significant and negative relationship to income inequality, namely the EP2 indicator which is the percentage of households with a source of lighting (PLN). The participating control variables show that the results have an effect on income inequality in Indonesia